Health Outcomes of Unpaid Caregivers in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis - Magana-Frade, I; Martinez-Diaz, P; Loyola-Fuentes, M (Blackwell Publishing Ltd, 2020)
Aims and objectives: To explore differences in health outcomes between unpaid caregivers and noncaregivers living in low- and middle-income countries (LMICs). Background: Previous meta-analyses found worse health outcomes for unpaid caregivers in high-income nations. However, no meta-analysis has considered unpaid caregivers from LMICs. A systematic integration of this topic may contribute to nursing care for unpaid caregivers in LMICs. Design: Systematic review and meta-analysis of observational studies. Methods: Following PRISMA statement, studies were searched for using the CINAHL, PubMed and SciELO databases, limited to publications until 31 December 2019. Random- and fixed-effects meta-analyses were used for data synthesis. Results: Fourteen studies from Africa, Asia and South America were included. Unpaid caregivers of people with ill-health were more anxious and depressed than noncaregivers. Studies conducted in Asia and South America reported poorer health outcomes for unpaid caregivers than noncaregivers, whereas the trend for African studies was the opposite. Unpaid caregivers of healthy individuals may have better health status than noncaregivers, particularly those caring between 1–14 hr per week. Of the six studies which examined gender differences, two studies informed worse health outcomes for women, one presented the opposite effect, and three found no differences. Conclusions: Individual, social, cultural and systemic factors play an important role in the health outcomes of unpaid caregivers in LMICs. More evidence is needed from LMICs. As unpaid caregivers are predominantly female, urgent attention to the health outcomes of female unpaid caregivers is required. Relevance to clinical practice: The management of mental health problems, particularly anxiety and depression, should be an integral part of nursing care for unpaid caregivers living in LMICs. To further promote the health of unpaid caregivers in developing countries, stakeholders should consider launching educational campaigns that assist caregivers in finding ways to meet their cultural obligations while also reinforcing caregiver self-care. © 2020 John Wiley & Sons Ltd